Can Emotional Intelligence and Forgiveness bring a Difference? Comparison between Clinically Diagnosed Individuals and Normal Population - Umair Ahsan, Roomana Zeb, Saima Arzeen (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The aim of the current study was to determine whether the absence of positive qualities such as emotional intelligence and forgiveness contribute to the occurrence of psychopathology. Method: To achieve this objective, a group of 150 participants (n=100 psychologically healthy; n=50 psychologically disturbed) was chosen using a purposive convenience sampling technique. The participants varied in terms of age (18-50 years), gender, education, and socioeconomic status. The researchers administered the Schutte Self Report Emotional Intelligence Test (SSEIT,2009) and the Heartland Forgiveness Scale (2005) to the sample. Findings/Results: The findings indicated a significant predictive relationship between emotional intelligence and forgiveness, highlighting their positive influence. Conclusion: Moreover, a noteworthy distinction was observed between psychologically disturbed individuals and the general public regarding both emotional intelligence and forgiveness. Keywords: Emotional Intelligence, Forgiveness, Psychopathology